Implementasi Pemberian Kredit Usaha Rakyat (KUR) pada KSP Kopdit Obor Mas Cabang Pasar Tingkat - Angelina Lale Buu; Yosefina Andia Dekrita; Yoseph Darius Purnama Rangga (Jurnal Simki Economic, 2024)
This study aims to explain the implementation of People's Business Credit (KUR) at the KSP of the Obor Mas Cooperative Market Level Branch. The research method used is descriptive qualitative research. Data collection techniques are carried out by triangulation (combined observation, interviews, documentation). The subjects in this study included employees at KSP Kopdit Obor Mas Pasar Level Branch. The results showed that the Implementation of People's Business Lending (KUR) at the KSP Kopdit Obor Mas Pasar Level Branch has implemented the provision of KUR. In the implementation of the provision of people's business loans, the KSP Kopdit Obor Mas implements the provision of KUR in accordance with the provisions of KUR services regulated in the Regulation of the Minister of Cooperatives for Economic Affairs of the Republic of Indonesia No. 1 of 2023 concerning amendments to the regulation of the Coordinating Minister for Economic Affairs of the Republic of Indonesia No. 1 of 2022 concerning guidelines for the implementation of people's business loans.